A dose- rather than delivery profile-dependent mechanism regulates the "muscle-full" effect in response to oral essential amino acid intake in young men - Mitchell, William Kyle; Phillips, Beth E.; Williams, John P.; Rankin, Debbie; Lund, Jonathan N.; Smith, Kenneth; Atherton, Philip J. (American Society for Nutrition, 2015)
Background: The anabolic response of skeletal muscle to essential amino acids (EAAs) is dose dependent, maximal at modest doses, and short lived, even with continued EAA availability, a phenomenon termed “muscle-full.” However, the effect of EAA ingestion profile on muscle metabolism remains undefined.